Building Secure Wireless Networks with 802.11 - Khan, Jahanzeb (Wiley Publishing, 2011)
Provides a step-by-step approach for planning and implementing a wireless LAN based on 802.11 Wireless Fidelity (Wi-Fi) technology Authors are Wi-Fi security experts who are able to address the firestorm of concerns about security for 802.11b networks Offers a clear perspective of interoperability with related wireless standards like 802.11a, HomeRF, and Bluetooth Explains how to achieve the same performance as a wired Ethernet connection and deliver flexibility and high speed